DEA Approach Towards Exploring the Sustainability of Funding in Higher Education. Empirical Evidence from Romanian Public Universities - Dalina Dumitrescu; Ionela Costică; Liliana Nicoleta Simionescu; Ștefan Cristian Gherghina (Amfiteatru Economic)
The present paper evaluates the Romanian public universities from funding efficiency point of view over the past 7 years, respectively 2012-2018. In order to evaluate the funding efficiency, we employed a nonparametric method, namely data envelopment analysis (DEA) for three-cycle system (technical efficiency from constant return to scale, technical efficiency from variable return to scale and scale efficiency). Based on our empirical findings 11 universities showed to be efficient when we applied VRS and only two universities with CRS approach. When scale efficacy was applied, our sample reduced to only two public universities as being efficient. This study identifies characteristics that describe differences within the public universities efficiency based on funding in higher education system in Romanian